Perceptions of physics teachers and students in Indonesian senior high schools toward the changes of National Examination to Minimum Competency Assessment - Darul Wasilah, Dalfa; Ismail, Ali (Research in Physics Education, 2022)
The National Examination is a refinement of learning evaluation carried out by elementary school to high school students, and is held every year, the implementation of this exam aims to improve the quality of education in Indonesia. Although the implementation is held regularly, the facts show that the quality of education in Indonesia is still low. In accordance with the results of PISA and TIMSS which show that Indonesia is in the bottom 10, it means that Indonesian students are still low in terms of literacy and science. This fact changed the evaluation of education which originally used the National Examination, was changed to a Minimum Competency Assessment. The rolling out of this new assessment since 2021 will certainly change the views of teachers and students on the learning they are doing. Therefore, this study aims to investigate the perceptions of high school students and teachers regarding various aspects of changes in classroom learning, especially physics subjects since the minimum competency assessment was launched. This study uses non-experimental quantitative methods with questionnaires and interviews data collection methods. The questionnaire data analysis used descriptive statistics while the interview data analysis used thematic analysis. By using purposive sampling technique, the participants in this study were 6 high school physics teachers and 172 high school students. The results of the study revealed that most of the students and teachers agreed with the change of the National Examination to the Minimum Competency Assessment in terms of juridical, pedagogical, and psychological aspects.